Gait Speed among Older Participants Enrolled in an Evidence-Based Fall Risk Reduction Program: A Subgroup Analysis - Cho, Jinmyoung; Smith, Matthew Lee; Shubert, Tiffany E.; Jiang, Luohua; Ahn, SangNam; Ory, Marcia G. (Frontiers in Public Health, 2015)
.